2021
DOI: 10.3390/nano11071710
|View full text |Cite
|
Sign up to set email alerts
|

Solution Processed Zn1−x−ySmxCuyO Nanorod Arrays for Dye Sensitized Solar Cells

Abstract: Cu- and Sm-doped ZnO nanorod arrays were grown with 1 wt% of Sm and different weight percents (0.0, 0.5, 1.0 and 1.5 wt%) of Cu by two-step hydrothermal method. The influence of Cu concentration and precursor of Sm on the structural, optical and photovoltaic properties of ZnO nanorod arrays was investigated. An X-ray diffraction study showed that the nanorod arrays grown along the (002) plane, i.e., c-axis, had hexagonal wurtzite crystal structure. The lattice strain is present in all samples and shows an incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…With the continuous expansion of the application field of ceramic materials, higher requirements have been put forward for the shape, size, and forming accuracy of ceramic components. Gelcasting technology has been confirmed to be the most effective method to achieve near net shaping of ceramic products with larger sizes and more complex shapes because it can improve the deformation shrinkage and post-processing difficulties of traditional ceramic green body molding methods. …”
Section: Introductionmentioning
confidence: 99%
“…With the continuous expansion of the application field of ceramic materials, higher requirements have been put forward for the shape, size, and forming accuracy of ceramic components. Gelcasting technology has been confirmed to be the most effective method to achieve near net shaping of ceramic products with larger sizes and more complex shapes because it can improve the deformation shrinkage and post-processing difficulties of traditional ceramic green body molding methods. …”
Section: Introductionmentioning
confidence: 99%
“…However, ILs are well designed, which allows one to design functionalized IL mixtures by combining suitable anions and cations [7][8][9][10]. IL mixtures have been widely used in electrochemistry, carbon dioxide capture, biomass treatment, catalysis, extraction, and other fields [11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…DSSCs consist of several important components, a conductive substrate, a nanostructure semiconductor (electrode), a counter electrode, an electrolyte, and a visible-light absorber dye [8]. Previous studies have shown that ZnO nanorods with oriented and orderly epitaxial growth structures are very important for the development of new photovoltaic efficiencies of 3.15-4.46% [1], [5], [9], [10]. Various methods have been successfully used for the synthesis of ZnO nanorods, such as low-temperature solution [11], chemical bath deposition [12], precipitation [13], pyrolysis [14], a sol-gel dip-coating technique [5], and sputtering [15].…”
mentioning
confidence: 99%